Biofunctionalization of natural fiber-reinforced biocomposites for biomedical applications - Tavares, Tânia Daniela Eugénio (2020)
In the last ten years, environmental consciousness has increased worldwide, leading to the development of eco-friendly materials to replace synthetic ones. Natural fibers are extracted from renewable resources at low cost. Their combination with synthetic polymers as reinforcement materials has been an important step forward in that direction. The sustainability and excellent physical and biological (e.g., biocompatibility, antimicrobial activity) properties of these biocomposites have extended their application to the biomedical field. This paper offers a detailed overview of the extraction and separation processes applied to natural fibers and their posterior chemical and physical modifications for biocomposite fabrication. Because of the requirements for biomedical device production, specialized biomolecules are currently being incorporated onto these biocomposites. From antibiotics to peptides and plant extracts, to name a few, this review explores their impact on the final biocomposite product, in light of their individual or combined effect, and analyzes the most recurrent strategies for biomolecule immobilization.